2011
DOI: 10.1002/jcb.23259
|View full text |Cite
|
Sign up to set email alerts
|

Substance P signaling mediates BMP-dependent heterotopic ossification

Abstract: Heterotopic ossification (HO) is a disabling condition associated with neurologic injury, inflammation, and overactive BMP signaling. The inductive factors involved in lesion formation are unknown. We found that the expression of the neuro-inflammatory factor Substance P (SP) is dramatically increased in early lesional tissue in patients who have either fibrodysplasia ossificans progressiva (FOP) or acquired HO, and in three independent mouse models of HO. In Nse-BMP4, a mouse model of HO, robust HO forms in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
126
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 72 publications
6
126
0
Order By: Relevance
“…Since these cells are behind the blood-nerve barrier [26], it is difficult to envision how BMP2 enters this location. However, the timing appears to be similar to induction of the neuro-inflammatory pathways previously described [12, 14]. The lack of PS + cells in the soft tissues outside the nerve may be a direct result of rapid binding of BMP2 by inhibitory binding proteins in the region [27].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Since these cells are behind the blood-nerve barrier [26], it is difficult to envision how BMP2 enters this location. However, the timing appears to be similar to induction of the neuro-inflammatory pathways previously described [12, 14]. The lack of PS + cells in the soft tissues outside the nerve may be a direct result of rapid binding of BMP2 by inhibitory binding proteins in the region [27].…”
Section: Discussionmentioning
confidence: 66%
“…One of the earliest steps in the process is the remodeling of the epineurial or outer matrix structure of the peripheral nerves [7, 12] [13] near the site of HO and associated neurogenic inflammation [12, 14]. This process involves mast cells, which degranulate and contribute to the activation of the sympathetic nervous system [12] ultimately leading to the formation of brown adipocytes from cells derived from the perineurial layer of the peripheral nerves [13].…”
Section: Introductionmentioning
confidence: 99%
“…Removal of the epineurium was correlated with migration of progenitors that reside in the perineurium that undergo brown adipogenesis [34], presumably for the purpose of patterning the new bone [27]. Blocking this process either through delivery of inhibitors of mast cell degranulation [33] or inhibitors of the binding of pain mediators to their receptor [13] resulted in a significant decrease in HO. Blocking nerve remodeling led to the accumulation within the endoneurium of nanog + Klf-4 + osterix + progenitors [33].…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that substance P might be one of systemic factors responsible for HO in mouse models of FOP [36,126]. Salisbury et al have shown that BMP-2 stimulation of substance P and calcitonin gene related peptide increased concentration of substance P in muscle [36].…”
Section: Sca1mentioning
confidence: 99%
“…Firstly, as studies on humans are retrospective, there is no study on the earliest stages of NHO to identify the early cellular and molecular events leading to heterotopic ossification in muscles and joints. Secondly, there is no unmodified animal model of NHO after central nervous system lesions [125,126]. The only existing animal models of HO are genetically modified mouse models of 1) progressive osseous heteroplasia, where HO is developed subcutaneously and caused by inactivating mutations of the GNAS gene [127], and 2) FOP in which activating mutations of ACVR1 are introduced as a transgene or knocked-in the endogenous mouse Acvr1 gene [48], or in which BMP-4 or BMP-2 are overexpressed by means of transgenes or recombinant adenoviruses [36,125,128].…”
Section: Introductionmentioning
confidence: 99%